A procura de uma nova vida: histórias orais de migrantes nordestinos em Vicentina/MS a partir de 1950. - Moura, Douglas Martins Lima de (2024)
The present study aims to work on the migration and memory of northeasterners in the formation in the municipality of Vicentina/MS, in which the CAND (Colônia Agrícola Nacional Dourados) is located, created by Getúlio Vargas during the Estado Novo period, northeasterners saw the possibility of a new place to rebuild their lives, devastated mainly by the climatic factor of droughts that made their lands unproductive. In this sense, memory appears as an expression of the oral history of life. It comprises the analysis of the trajectory of men and women who arrived in the city of Vicentina/MS from the 1950s onwards, with the investigation of the oral memory of these subjects, understanding the ways of working, family relationships, the experiences of what it means to be a northeastern migrant, and the leading role played in that municipality, when narrating their stories, portray the speech of a story that on a larger scale covers the national territory, which is the migration of northeasterners to all corners of this country. Therefore, their memories are individual, but also collective, considering that they talk about themselves, but also about a shared history, under the auspices of a group of northeasterners who are part of local history.